Solve for u -2u-14=-5(u+7)

Math
-2u-14=-5(u+7)
Simplify -5(u+7).
Tap for more steps…
Apply the distributive property.
-2u-14=-5u-5⋅7
Multiply -5 by 7.
-2u-14=-5u-35
-2u-14=-5u-35
Move all terms containing u to the left side of the equation.
Tap for more steps…
Add 5u to both sides of the equation.
-2u-14+5u=-35
Add -2u and 5u.
3u-14=-35
3u-14=-35
Move all terms not containing u to the right side of the equation.
Tap for more steps…
Add 14 to both sides of the equation.
3u=-35+14
Add -35 and 14.
3u=-21
3u=-21
Divide each term by 3 and simplify.
Tap for more steps…
Divide each term in 3u=-21 by 3.
3u3=-213
Cancel the common factor of 3.
Tap for more steps…
Cancel the common factor.
3u3=-213
Divide u by 1.
u=-213
u=-213
Divide -21 by 3.
u=-7
u=-7
Solve for u -2u-14=-5(u+7)

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top